Marketing Mix Strategy for Pilgrimage Tourism at the Cathedral Museum Jakarta in Efforts to Enhance the Attraction for International Tourists - Susanto, Prayogo; Fernanda, Dea (Universitas Wiralodra, 2024)
The Cathedral Museum is the only Catholic religious museum in Jakarta. Located in the Jakarta Cathedral Church in Central Jakarta, the museum narrates the history of Catholicism's development in Indonesia. The research aims to analyze the marketing mix strategy for pilgrimage tourism to enhance the attraction of international tourists to visit the Jakarta Cathedral Museum, thereby increasing the country's foreign exchange earnings. The researcher seeks to further understand the appropriate marketing mix communication strategies.The purpose of this research is to identify suitable marketing mix strategies that can be recommended to the museum. This type of research employs qualitative methods, including data collection through observation, interviews, and documentation. The research utilizes marketing mix theory and communication strategies to make future adjustments. This paper intends to conduct further research on the Jakarta Cathedral Museum to help international tourists learn about and visit the museum. Additionally, it aims to apply these findings to other museums and hopes to encourage the establishment of more religious museums that detail the arrival of religions in Indonesia.